2017
DOI: 10.1371/journal.ppat.1006270
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell tropism is a determinant of H5N1 pathogenesis in mammalian species

Abstract: The cellular and molecular mechanisms underpinning the unusually high virulence of highly pathogenic avian influenza H5N1 viruses in mammalian species remains unknown. Here, we investigated if the cell tropism of H5N1 virus is a determinant of enhanced virulence in mammalian species. We engineered H5N1 viruses with restricted cell tropism through the exploitation of cell type-specific microRNA expression by incorporating microRNA target sites into the viral genome. Restriction of H5N1 replication in endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 66 publications
0
55
0
Order By: Relevance
“…The importance of a functional endothelial barrier was demonstrated in a model of E. coli pneumonia, in which blockade of the interaction between integrin αvβ3 and its binding partner IQGAP1 at the endothelial cell-cell junction led to excesses in lung extravascular plasma and water, as well as increased lung weight within just 5 h of infection (216). It has also been shown that influenza infection can lead to vascular leak (217,218). This loss of barrier integrity stems, at least in part, from active infection of endothelial cells by influenza virus.…”
Section: Pulmonary Endothelial Cell Tolerance Mechanisms Endothelial mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of a functional endothelial barrier was demonstrated in a model of E. coli pneumonia, in which blockade of the interaction between integrin αvβ3 and its binding partner IQGAP1 at the endothelial cell-cell junction led to excesses in lung extravascular plasma and water, as well as increased lung weight within just 5 h of infection (216). It has also been shown that influenza infection can lead to vascular leak (217,218). This loss of barrier integrity stems, at least in part, from active infection of endothelial cells by influenza virus.…”
Section: Pulmonary Endothelial Cell Tolerance Mechanisms Endothelial mentioning
confidence: 99%
“…Cytokine storm following pulmonary infection is detrimental to the host, as limiting its magnitude has been shown to improve survival. For example, limiting H5N1 influenza infection in endothelial cells using microRNAs both reduced cytokine storm and improved survival (218). Similarly, treatment with an S1P1 antagonist during influenza infection reduced mortality in an endothelial cell-specific manner (226).…”
Section: Contribution Of Endothelial Cells To Cytokine Stormmentioning
confidence: 99%
“…Over the past 20 years, H5N1 viruses from infected domestic poultry have crossed the species barrier, causing severe and often fatal infections in humans with mortality rates as high as 60% (9). Many of the viral components critical for the enhanced virulence of H5N1 have been identified through the generation of recombinant and/or reassortant viruses (10) (11, 12). Prior studies have shown that the multibasic cleavage site (MBS) in the viral hemagglutinin of H5N1 facilitates higher viral replication and mediates extrapulmonary spread (13-15).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that the multibasic cleavage site (MBS) in the viral hemagglutinin of H5N1 facilitates higher viral replication and mediates extrapulmonary spread (13-15). In addition, our group has recently demonstrated that the endothelial cell tropism of H5N1 contributes to barrier disruption, microvascular leakage, and subsequent mortality (12). Moreover, polymorphisms that increase viral replication have been identified in the viral polymerase subunits of H5N1 strains (16-20).…”
Section: Introductionmentioning
confidence: 99%
“…Influenza A virus infections of extrapulmonary tissues, including the heart, spleen, kidney, thymus, and brain have been reported for various mouse models of infection (Fislova et al, 2009;Kotaka et al, 1990;Tundup et al, 2017). However, relevant models in which significant cardiac pathogenesis occurs are lacking, thus hindering advancement in the study of cardiac complications of influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%